Gender differences between the three dimensional gait analysis data of young athletes (Annals of Medical Research, 2021)
Aim: There are differences in skeletal structures between genders. These differences also have an impact on the gait patterns of individuals. The primary purpose of this study was to examine the differences between two genders with regard to gait parameters of young Turkish athletes. The secondary purpose was to form a representative gait sample of Turkish athletes.Material and Methods: A total of 51 athletes; 29 females, 22 males (5-18 years, mean age: 11.7) who did not have any disease that might lead to gait pathology were included in the study. Three-dimensional gait analysis was performed on all participants with ViconBonita System (Oxford Metrics Ltd., Oxford, England). Temporo-spatial, kinematic, and kinetic variables were compared among the groups.Results: Regarding the time-distance parameters; step distance (p=0.001) and stride length (p=0.002) were found to be greater in girls than in boys. The kinematic analysis showed that the maximum hip extension during the stance phase (H2, p=0.03) was greater in boys compared to the extension during the stance phase of the girls. The maximum hip flexion during the swing phase (H3, p=0.02), maximum hip adduction (H4, p=0.01) and maximum ankle plantar flexion (A3, p=0.04) were found to be higher in girls than in boys.Conclusion: The gait analysis data had significant gender differences. Sport technology and biomechanics have been advancing rapidly. We suggest that normal data and biomechanical factors will be clearer as the gait analysis results of the athletes increase.
Keywords: 3-D gait analysis; gait; gender; gender recognition; gender differences